ARISTOPHANES' ECCLESIAZVSAE AND THE REMAKING OF THE ΠΑΤΡΙΟΣ ΠΟΛΙΤΕΙΑ*. (9th September 2016) - Sheppard, Alan
Abstract : Ecclesiazusae, the first surviving work of Aristophanes from the fourth centuryb.c.e., has often been dismissed as an example of Aristophanes' declining powers and categorized as being less directly rooted in politics than its fifth-century predecessors owing to the after-effects of Athens' defeat in the Peloponnesian War. Arguing against this perception, which was largely based on the absence of ad hominem attacks characterizing Aristophanes' earlier works, this paper explores how Ecclesiazusae engages with contemporary post-war Athenian politics in a manner which, while different to his earlier comedies, remained closely rooted in the political and cultural concerns of the 390s. By examining the figure of Praxagora, I will first consider recent suggestions that Ecclesiazusae hints at the possibility of an anti-democratic coup. I will then examine how contemporary discussions of constitutional and legal reforms (including the invocation of 'founding fathers' such as Solon and Lycurgus) are incorporated into both Praxagora's language and the scenes featuring the Selfish Man and Hags that follow the establishment of Praxagora's regime. Examining these final scenes, I conclude that Ecclesiasuzae does not suggest that the idea of democratic equality itself is fundamentally flawed, but instead argues that Athens needs a suitable leader, well suited to the rough and tumble of assembly rhetoric, in order to successfully function. In the world of Ecclesiazusae, the men of Athens have failed too often to inspire any hope, putting their own interest above the state, and the new leader must be someone different. Thus Aristophanes sets up Praxagora as a female Solon to remake the state and lead the democracy. The second half of the play demonstrates this need for a strong leader, as problems arise both from the quarter of critical bystanders (the Selfish Man and Epigenes, the Young Man in the 'hag scene') and from over-zealous enforcers (the Old Women).